2005
DOI: 10.1103/physrevb.72.174113
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale clusters in the high performance thermoelectricAgPbmSbTem+2

Abstract: The local structure of the AgPbmSbTem+2 series of thermoelectric materials has been studied using the atomic pair distribution function (PDF) method. Three candidate-models were attempted for the structure of this class of materials using either a one-phase or a two-phase modeling procedure. Combining modeling the PDF with HRTEM data we show that AgPbmSbTem+2 contains nanoscale inclusions with composition close to AgPb3SbTe5 randomly embedded in a PbTe matrix.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 15 publications
2
41
0
2
Order By: Relevance
“…It has been observed that the LAST-m alloys are inhomogeneous at nanoscale with at least two phases. The minority phase rich in Ag and Sb is in nanosize and is endotaxially embedded in the majority phase that is poor in Ag and Sb, and the electronic structure of LAST-m materials depends sensitively on the perturbation resulting from the Ag and Sb atoms [2][3][4]. The nanoinclusions in the alloys are considered to play a role similar to the quantum dots in the molecular beam epitaxy grown PbSe 0.98 Te 0.02 /PbTe superlattices [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the LAST-m alloys are inhomogeneous at nanoscale with at least two phases. The minority phase rich in Ag and Sb is in nanosize and is endotaxially embedded in the majority phase that is poor in Ag and Sb, and the electronic structure of LAST-m materials depends sensitively on the perturbation resulting from the Ag and Sb atoms [2][3][4]. The nanoinclusions in the alloys are considered to play a role similar to the quantum dots in the molecular beam epitaxy grown PbSe 0.98 Te 0.02 /PbTe superlattices [5].…”
Section: Introductionmentioning
confidence: 99%
“…Such good thermoelectric properties were supposed to be related to some AgSb-rich nano-dots in the materials. The compositional fluctuations on the nano-sized level caused a quantum nano-structure, which is the key reason for the reduction in thermal conductivity [19][20][21] , hence enhancing the figure of merit. Compared with thermoelectric films, thermoelectric bulk materials are conducive to realization of large temperature difference and industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…However these materials are not conventional bulk but composites (see below In 2 O 3 + Ge). High resolution transmission microscopy have shown that Ag-Sb rich phase nanocrystals exist in a Pb-Te rich matrix, that has also been described as nano-clusters of AgPb 3 SbTe 5 in PbTe matrix [Lin 2005]. Such nano-phases could be responsible of high ZT values, theoretically predicted, and observed in quantum wells superlattice, nano-dots etc.. (see below nano-materials).…”
Section: 4b Derivatives From Pbte and Tagsmentioning
confidence: 96%